Self Assessment For Student Performance Based on Higher Order Thinking Skills in Physics Learning - Wulan Trisnawaty; Alfina Citrasukmawati; M. Anas Thohir (Journal of Education and Learning (EduLearn), 2017)
This research is aimed to develop Self Assessment Based on Higher Order Thinking Skills (SSA-HOTS) instrument in learning physics to train student’s higher order thinking Skills. The development model using 4D from Thiagarajan with the subjects of the study was selected by random at high school student of IPA Major. Data collection techniques include test, observation, and questionnaire distribution then analyzed using correlation test. From the result of the research, it is found that the developed instrument is deserve to use, high reliability value, difficulty of problem proportional, and test item sensitive. Correlation assessment between student and teacher on cognitive, psychomotor, and affective aspects on the character of honesty and cooperation each 0.95; 0.83; 0.81; And 0.80 are in the high category. Students also responded positively to this instrument. So it can be concluded that the self assessment instrument based on Higher Order Thinking Skills is deserve to be used to train student higher order thinking skills.